(untitled) (Tanzania Journal for Population studies and Development, 2021)
The debate on the relationship between population growth and economic growth has been enduring and varies across countries. While the first theory on population and economic growth states that population growth stimulates economic growth, the second theory views population growth as a factor that adversely affects economic growth. The third school of thought posits that population growth is a neutral factor in economic growth, and is determined outside standard growth models. Given this situation, there was a need to establish the relationship between economic growth and population growth in Tanzania. The study employed the Vector Auto-regression (VAR) estimation technique, and used annual time series data from 1971 to 2017. The results indicate that economic shocks due to population growth are positive and negative. This could be attributed to unstable expenditure on healthcare by the government in the improvement of child survival through various government programmes. The study concludes that, in Tanzania, population growth promotes economic growth and, subsequently, economic development. The study recommends that the government should ensure that the economy grows at a higher rate than population growth. This will ensure that the increasing demand for services arising from population growth is met. Having a large, healthier, and better-educated workforce will only bear economic fruit if the extra workers can find jobs.